2015
DOI: 10.1186/s12888-015-0420-2
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship and recovery: two intertwined concepts for civic-recovery

Abstract: BackgroundValidation of the psychometric properties of a new measure of citizenship was required for a research project in the province of Quebec, Canada. This study was meant to study the interplay between recovery- and citizenship-oriented supportive employment. As recovery and citizenship were expected to be two related concepts, convergent validity between the Citizenship Measure (CM) and the Recovery Assessment Scale (RAS) was tested.MethodsStudy objectives were to: 1) conduct exploratory factor analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
2
41
0
4
Order By: Relevance
“…Participants in our study scored lower on self-efficacy (M = 23.82, SD = 6.70) than a sample of individuals with schizophrenia M = 26.3, SD = 6.8 (Vauth et al, 2007), although the sample size and the treatment status of the participants differed across these studies. Since there are different versions of the Recovery Attitudes Scale (RAS-41, 24 to 22 scales) Pelletier et al, 2015), we were unable to identify other research studies using the smaller scale consisting of 22 items and therefore could not make comparisons with other populations of people with eating disorders and mental illnesses. Finally, consistent with our findings, previous research has shown that lower rates of internalized stigma are associated with higher attitudes towards recovery or recovery expectations (Corrigan, 2008;Muñoz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study scored lower on self-efficacy (M = 23.82, SD = 6.70) than a sample of individuals with schizophrenia M = 26.3, SD = 6.8 (Vauth et al, 2007), although the sample size and the treatment status of the participants differed across these studies. Since there are different versions of the Recovery Attitudes Scale (RAS-41, 24 to 22 scales) Pelletier et al, 2015), we were unable to identify other research studies using the smaller scale consisting of 22 items and therefore could not make comparisons with other populations of people with eating disorders and mental illnesses. Finally, consistent with our findings, previous research has shown that lower rates of internalized stigma are associated with higher attitudes towards recovery or recovery expectations (Corrigan, 2008;Muñoz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Conceptual overlap between models of recovery proposed within the two fields suggests that tools developed within mental health may also be applied within a trauma population, but population‐specific differences (Chouliara et al, ) highlight the need for further testing before these can be confidently applied in practice. Although personal recovery measures have been psychometrically examined within samples that include people with a diagnosis of PTSD (Pelletier et al, ), and alongside measures related to post‐traumatic growth (Moran et al, ), no research has yet evaluated the validity of personal recovery measures exclusively within a population of people with experience of trauma. This paper therefore seeks to evaluate the psychometric properties of one such recovery measure, the Individual Recovery Outcomes Counter (I.ROC), in a trauma population.…”
Section: Introductionmentioning
confidence: 99%
“…Ces progrès, réalisés il y a plus de 200 ans maintenant, sont-ils encore d'actualité pour des pratiques psychiatriques axées sur le patient et son rétablissement civique à titre de citoyen à part entière (Pelletier, Corbière, Lecomte, Briand, Corrigan, Davidson et Rowe, 2015) ? Dans cet article nous nous demandons si les constats dressés par Pussin et Pinel, à l'âge d'or de l'enfermement des personnes atteintes de maladies mentales, n'étaient pas en fait si avant-gardistes que nous commençons à peine à les saisir et à les appliquer à nos pratiques postasilaires contemporaines.…”
Section: Résumé De L'articleunclassified